2001
DOI: 10.1121/1.1381026
|View full text |Cite
|
Sign up to set email alerts
|

A computational sensorimotor model of bat echolocation

Abstract: A computational sensorimotor model of target capture behavior by the echolocating bat, Eptesicus fuscus, was developed to understand the detection, localization, tracking, and interception of insect prey in a biological sonar system. This model incorporated acoustics, target localization processes, flight aerodynamics, and target capture planning to produce model trajectories replicating those observed in behavioral insect capture trials. Estimates of target range were based on echo delay, azimuth on the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…An interesting possibility is the cross-modal integration of the visual background with the auditory foreground: the bat could follow a CATD strategy by maneuvering such that silhouettes of foliage against the night sky, or the positions of the moon or bright stars (any distant, high contrast object) appear stationary with respect to the acoustically derived position of the target. Some previous modeling studies of bat pursuit behavior have suggested that bats can successfully capture insects using a nonpredictive strategy [ 25, 26], whereas another modeling study has proposed that bats use an internal model of target motion to predictively pursue an insect [ 27]. Our experimental results show that the bat uses a functionally predictive strategy (CATD).…”
Section: Discussionmentioning
confidence: 67%
“…An interesting possibility is the cross-modal integration of the visual background with the auditory foreground: the bat could follow a CATD strategy by maneuvering such that silhouettes of foliage against the night sky, or the positions of the moon or bright stars (any distant, high contrast object) appear stationary with respect to the acoustically derived position of the target. Some previous modeling studies of bat pursuit behavior have suggested that bats can successfully capture insects using a nonpredictive strategy [ 25, 26], whereas another modeling study has proposed that bats use an internal model of target motion to predictively pursue an insect [ 27]. Our experimental results show that the bat uses a functionally predictive strategy (CATD).…”
Section: Discussionmentioning
confidence: 67%
“…The stopping distance can be estimated by combining information on the initial velocity of the bat, maximal deceleration, and sensorimotor time delay. Taking a representative bat cruising velocity of 5 m/s [25], a maximal deceleration of 15 m/s 2 (estimated from a sample trajectory in [25]), and an estimated sensorimotor delay of 100–200 ms [30] yields an estimated stopping distance in the range of 130–180 cm. Although there is a great deal of uncertainty in these estimates, the stopping distance of the bat seems comparable to the sensory range for prey detection.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, none of the numerous models built to understand animal perception (Neumann, 2002;Ritz et al, 2000;Svensen and Kiorboel, 2000;Erwin et al, 2001), has ever incorporated the potential structural variability of a sensor to predict consequences on the performance of animals. Notable exceptions are the recent studies performed by Spaethe et al (2001) and Spaethe and Chittka (2003) who suggest that interindividual variation in the morphology of the compound eye and the performance of the linked neural circuitry influences foraging efficiency of bumblebees under natural conditions.…”
Section: Sensor Performancementioning
confidence: 99%